2021
DOI: 10.1093/bjc/azab035
|View full text |Cite
|
Sign up to set email alerts
|

Sexual violence as a sexual script in mainstream online pornography

Abstract: This article examines the ways in which mainstream pornography positions sexual violence as a normative sexual script by analysing the video titles found on the landing pages of the three most popular pornography websites in the United Kingdom. The study draws on the largest research sample of online pornographic content to date and is unique in its focus on the content immediately advertised to a new user. We found that one in eight titles shown to first-time users on the first page of mainstream porn sites d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…Media coverage which often precedes vast public discussion on social media. Considerable theorizing and research now exists that attempts to explain such sexual violence and aggression ( Johnson and Beech, 2017 ; Blagden et al, 2018 ; Willmott et al, 2018 ; Chan, 2021 ; Vera-Gray et al, 2021 ), with notable Forensic Psychologists such as the late Dr. Ruth Mann, devoting entire careers in pursuit of effective interventions that reduce and prevent sexual recidivism (see Mann and Rollnick, 1996 ; Mann, 2004 , 2011 , 2016 ; Mann et al, 2019 ). The consequences of sexual offending on victim-survivors and families are also understood well ( Boduszek et al, 2019 ; Chowdhury et al, 2021 ; Debowska et al, 2021 ; Duncan et al, 2022 ; Sharratt et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Media coverage which often precedes vast public discussion on social media. Considerable theorizing and research now exists that attempts to explain such sexual violence and aggression ( Johnson and Beech, 2017 ; Blagden et al, 2018 ; Willmott et al, 2018 ; Chan, 2021 ; Vera-Gray et al, 2021 ), with notable Forensic Psychologists such as the late Dr. Ruth Mann, devoting entire careers in pursuit of effective interventions that reduce and prevent sexual recidivism (see Mann and Rollnick, 1996 ; Mann, 2004 , 2011 , 2016 ; Mann et al, 2019 ). The consequences of sexual offending on victim-survivors and families are also understood well ( Boduszek et al, 2019 ; Chowdhury et al, 2021 ; Debowska et al, 2021 ; Duncan et al, 2022 ; Sharratt et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Wignall et al (2020) found British university students often assumed or negotiated consent based largely on interpretation of non-verbal cues. Considered alongside the frequency with which rough sex and sexual violence is presented as a normative sexual behavior on popular pornography platforms ( Vera-Gray et al, 2021 ), beliefs about consent to “rough sex” may well be obtained through interpretation of non-verbal information and based largely upon pre-existing sexual scripts that are frequently ill informed and problematic. Sexual scripts are individual criteria for appropriate sexual behavior, which provides a socially constructed framework for how to process our interactions during sexual conduct.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term, it may be particularly important to re-define scripts for male sexuality; doing so will be key for preventing sexual violence against women, but it will also provide a route for more fulfilling relationships for men. Practically, this could involve a continued feminist activism within sex education for younger people as well as a critical examination of pornography as being central to normalizing sexual violence and coercion in sexual scripts (Vera-Gray et al, 2021). As other men’s behaviors serve as powerful motivators for men, it is likely that male feminist activism in this area could yield considerable, long-term rewards (Gidycz et al, 2011; Wiley et al, 2012), particularly in the context of criticizing mainstream pornography.…”
Section: Discussionmentioning
confidence: 99%
“…As women's roles in society are changing more rapidly than men's (Ging, 2019), it is otherwise likely that men will feel "left behind," something that will only strengthen the backlash against feminism. This has been further elaborated on by Van Valkenburgh (2019) who recommends that future theorizing on online aggression against feminists consider the wider societal conditions-in particular neoliberalism-that create the foundations for the feminist backlash.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…
One of the first tasks of any porn researcher is to develop sets of skills for dealing with the zombie concepts, evidence and theories that underpin claims of the 'effects' of porn consumption, and sister arguments framed around discourses of harm. Those skills have been in considerable demand recently following the publication of an article in The British Journal of Criminology (Vera Gray et al 2021) that was uncritically circulated by almost every news outlet in the UK and abroad. Based on work undertaken by researchers in law, sociology and computing at Durham University, the article made confident claims that it had gathered 'the largest research sample of online pornographic content to date' to discover that 'one in eight titles shown to first-time users on the first page of mainstream porn sites describe sexual activity that constitutes sexual violence'.
…”
mentioning
confidence: 99%